A dynamic fALFF approach to assess emotional states in pilots through precuneus activity - Xi Chen; Peiran Xu; Qinsong Song; Shicong Zhang; Qingbin Meng; Qi Chu; Donglin Huang (Brain-Apparatus Communication)
Background Mental health in pilots has become a critical factor affecting flight safety in the aviation industry. Pilots face high-pressure work environments and long working hours, which can lead to mental health issues, potentially affecting their performance, impacting aviation safety.Methods We investigated the neural mechanisms underlying the mental health of civil aviation pilots by analyzing the fractional Amplitude of Low Frequency Fluctuations (dfALFF) using functional magnetic resonance imaging (fMRI). A total of 48 pilots and 39 healthy controls were included, and their emotional states were assessed using the Self-Rating Depression Scale (SDS) and Self-Rating Anxiety Scale (SAS). The dfALFF instability in the precuneus of the pilots was calculated and compared with that of the controls to explore the relationship between brain activity and emotional state.Results The results showed significantly higher dfALFF instability values in the precuneus of the pilots than in the control group. Additionally, instability in the precuneus was positively correlated with SDS and SAS scores.Conclusion These findings highlight the potential of precuneus dfALFF instability as a biomarker to assess pilots’ mental health. This study emphasizes the importance of incorporating neural activity indicators into pilot training and mental health assessments to enhance aviation safety and provide timely interventions for mental health issues.